Fostering Students’ Emotional Well Being and Character Development through School Based Counseling (A Case Study at SDN 163/X Catur Rahayu, East Tanjung Jabung, Jambi, Indonesia) - Sri Kadarsih (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2026)
Students’ emotional well being and character development are essential components of holistic education, particularly at the elementary school level, where children undergo significant social, emotional, and moral development. This study aims to examine the implementation of school based counseling in fostering students’ emotional well being and character development at SDN 163/X Catur Rahayu, East Tanjung Jabung, Jambi, Indonesia. Employing a qualitative case study approach, the research explores the forms of counseling services provided, the strategies employed by teachers and school personnel, and the ways in which these practices contribute to students’ emotional and character development. Data were obtained through in depth interviews, classroom and school observations, and documentation involving school leaders, teachers, counselors or counseling personnel, and students. The findings indicate that school based counseling contributes to students’ emotional well being by providing opportunities for them to express their feelings, develop emotional awareness, manage interpersonal conflicts, and receive individualized support when facing academic, social, or personal challenges. In terms of character development, counseling activities foster positive values such as responsibility, empathy, self-discipline, respect, honesty, and cooperation. The study further reveals that the effectiveness of counseling is strengthened by teachers’ consistent involvement, supportive teacher student relationships, collaboration among school stakeholders, and the integration of counseling principles into students’ daily school experiences. Nevertheless, several challenges remain, including limited counseling resources, the dual roles of teachers, and the need for more systematic counseling programs. Overall, the study demonstrates that school based counseling can serve as a strategic educational approach to promoting students’ emotional well being and character development when implemented collaboratively, continuously, and in accordance with students’ developmental needs.